Reciprocal Teaching Strategy for Improving Modern Arabic Text Reading Skills - Ade Nandang; Ruli Syaepul Azhar; Muhammad Fikri Fadhlullah (Tadris Al-'Arabiyyah: Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2026)
This study aims to examine the effect of the Reciprocal Teaching strategy on improving students’ reading skills in modern Arabic texts. The research employed a quantitative approach using a quasi-experimental design involving an experimental class and a control class. The sample consisted of 72 students selected through cluster random sampling. Data was collected through reading comprehension tests (pretest and posttest) and classroom observation, then analyzed using descriptive statistics and an independent sample t-test. The results indicate that the mean posttest score of the experimental class (84.31) was significantly higher than that of the control class (72.58). The t-test analysis showed a significant value of 0.000 (p < 0.05), indicating a statistically significant difference between the two groups. In addition, the percentage of improvement in the experimental class reached 37.1%, while the control class showed an improvement of only 17.0%. These findings demonstrate that the Reciprocal Teaching strategy has a significant effect on enhancing students’ reading skills in modern Arabic texts. Therefore, this strategy is effective as an alternative approach to qirā’ah instruction that promotes active participation and deeper reading comprehension.